2003
DOI: 10.1074/jbc.m210806200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inducible Nitric-oxide Synthase and Intracellular Protein Tyrosine Nitration in Vascular Smooth Muscle Cells

Abstract: A significant increase in the induction of inducible nitric-oxide synthase (iNOS) protein expression and in the levels of nitrite plus nitrate was observed in rat aortic smooth muscle cells (RASMCs) stably transfected with catalase (RASMC-2C2) as compared with empty vector-transfected RASMC-V4 cells after exposure to cytokines and lipopolysaccharide. The increased expression of iNOS protein in the RASMC-2C2 cells was associated with a significant activation of nuclear transcription factor B, one of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 52 publications
5
61
0
Order By: Relevance
“…Both treatments of APAP and LPS resulted in similar differences in hepatic protein nitration between the SOD1-/-and WT mice, despite a large variation (0 to 79%) of genotype differences in plasma NO concentrations. Although NO is needed for the formation of peroxynitrite and inhibition of NO synthesis attenuates protein nitration in some instances [28,51], protein nitration may take place at baseline of NO production, and thereby is not strictly dependent on elevated NO concentrations [24,26,28]. In fact, expression of inducible nitric oxide synthase in liver was not different between WT and the SOD1-/-mice (data not shown).…”
mentioning
confidence: 89%
“…Both treatments of APAP and LPS resulted in similar differences in hepatic protein nitration between the SOD1-/-and WT mice, despite a large variation (0 to 79%) of genotype differences in plasma NO concentrations. Although NO is needed for the formation of peroxynitrite and inhibition of NO synthesis attenuates protein nitration in some instances [28,51], protein nitration may take place at baseline of NO production, and thereby is not strictly dependent on elevated NO concentrations [24,26,28]. In fact, expression of inducible nitric oxide synthase in liver was not different between WT and the SOD1-/-mice (data not shown).…”
mentioning
confidence: 89%
“…In this context, oxyhemoglobin (oxyHb), present at 5 mM in red blood cells, serves as a sink to capture intravascularly formed nitrating species. Indeed, a fraction of intravascularly formed peroxynitrite could diffuse into red blood cells before enacting target molecule reactions with plasma components (83) and could undergo a fast reaction with oxyHb, which results in its isomerization to NO 3 Ϫ , without significant formation of nitrating species (82 (60,85). In cases where SOD is not close enough to O 2 Ϫ sources, it can enhance peroxynitritedependent nitration (7,8).…”
Section: Red Blood Cell Hemoglobin As a Sink Of Nitrating Speciesmentioning
confidence: 99%
“…MPO or EPO overexpresses are not available yet, but in the future they may also provide clues to the role of MPO and EPO in pathology. Enhanced removal of H 2 O 2 by stable transfection of cells with catalase can also be useful to assess the contribution of the hemeperoxidase pathway (60). The hemeperoxidaseindependent nitration observed in MPO and EPO knockouts (15) may be due, in addition to peroxynitrite, to the LMW metal-dependent pathway (12).…”
Section: Lessons From Geneticsmentioning
confidence: 99%
“…We as well as others have shown that NF-κB activity is potentiated by increased protein levels of catalase, although in this case the mechanisms of action have not been delineated [42,60]. As described in the next sections, the fact that cytokine-induced iNOS expression in rodent SMC requires the activation of ERK would also suggest that redoxregulation of NF-κB in this system would occur at the level or upstream of mitogen activated protein kinases.…”
Section: Regulation Of Inos Activity and Expressionmentioning
confidence: 91%
“…The nuclear transcription factor κB, a primary regulator of iNOS expression, is redox-regulated at multiple levels including the binding of NFκB to κB motifs [154], regulation of the IκB kinase complex [88], and potentially very upstream through control of the endosomal targeting of cytokine receptors and Nox [101]. Direct evidence that the redox environment may regulate iNOS expression in vascular smooth muscle cells has been obtained: increased levels of the antioxidant enzyme catalase increase NFκB activation and iNOS expression after cytokine stimulation of vascular smooth muscle cells [42,60]. These studies indicated that in this context cytokine-induced hydrogen peroxide production negatively regulates iNOS expression.…”
Section: Introductionmentioning
confidence: 99%